Teaching for projects for the course “Methodologies and techniques of the educational research” - Marzano, Antonio; Vegliante, Rosa; Miranda, Sergio; Formisano, Maria Anna (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2018)
Improving the quality of the offer in the higher education courses to encourage the insertion of the younger generations into the labour market, is one of the challenges coming from the Bologna Declaration (1999). This objective has to take into account the quality of the teaching/learning processes that, in turn, are inextricably linked to the methodological/didactic characteristics used in the different university classroom contexts. This paper aims to describe the pedagogical-didactic model of the course “Methodologies and techniques of educational research”, held in the first semester of the academic year. 2015/2016, at the University of Salerno and involving the students of the master's degree program of professional educators and experts in continuing education (LM57). The methodological approach used was the teaching for projects: the classroom activities, integrated by the use of information technology, were marked by moments of discussion and workgroups aimed at the realization of a research project. The aim of this work is showing the effectiveness of the used and highlighted teaching approach, on the one hand, by the participation and attendance of the students in the classroom activities and, on the other hand, by an overall improvement of the learning outcomes.